Konsep Al-Ghuslu dalam Kitab Fiqih Manhaji - Samidi K (Balai Penelitian dan Pengembangan Agama Semarang, 2010)
The Fikih Manhaji, written by Musthafa al-Khani and taught in some pesantrensin Indonesia, is regarded as a modern fiqh book. This writing is based upon a study of the book which uses qualitative method and descriptiveanalitical analysis. Although the Fikih Manhaji contains of three volumes, this study, however, is only focusing on the chapter of al-ghuslu (bathing) which is discussed in the first volume. Al-ghuslu is divided into two categories: mandi wajib (a must/obligatory bathing) and mandi sunnah (recommended bathing). In addition to giving the definition of the two groups, the book also discusses some examples of each category.